Evaluation of Silicon Nanonet Field Effect Transistor as Photodiodes - Muhammed Kayaharman; Maxime Legallais; Celine Ternon; Sangtak Park; Bassem Salem; Mehrdad Irannejad; Eihab Abdel-Rahman; Mustafa Yavuz (Proceedings, 2017)
Silicon nanowire networks (nanonets) is an emerging candidate technology for sensor applications. In this work, we characterized Field Effect Transistor (FETs) employing silicon nanonet channels and evaluated their performance as photodiodes. We found that shorter and higher density nanonet channels have lower resistance and higher current flow. The drain current of the FETs doubled when irradiated with a continuous wave He-Ne laser (wavelength 632 nm). Finally, we examined the long-term stability of the FETs. The channel resistance increased by one order-of-magnitude after 6 months of storage in open air.